Ten years after: findings from the medical surveillance program on Health Effects in High-Level Exposure to PCB (HELPcB) - Rengelshausen, Jens; Randerath, Isabella; Schettgen, Thomas; Esser, Andre; Kaifie, Andrea; Lang, Jessica; Kraus, Thomas; Ziegler, Patrick (Archives of Toxicology, 2023)
After the detection of high environmental and occupational exposure to polychlorinated biphenyls (PCBs) in a German recycling company for transformers and capacitors in 2010, the multidisciplinary medical surveillance program “HELPcB” (Health Effects in High-Level Exposure to PCB) was established for former PCB-exposed workers of the company, their family members, employees of surrounding companies, and area residents to investigate potential adverse health effects by PCB exposure in a longitudinal study approach with up to seven examination time points between 2010 and 2019. More than 300 individuals were enrolled into the program. Assessments particularly included plasma and urine concentrations of PCB congeners and their metabolites, clinical laboratory parameters, Comet assay, analysis of telomere length, neuropsychological examinations, psychological screening, abdominal and thyroid ultrasound examination. This review summarizes the main results of the studies conducted in the HELPcB program yielding relevant new data on potential adverse effects of PCB exposure in humans and potential mechanisms that underlie these effects. Even larger studies in PCB-exposed individuals are warranted to confirm the results of this program and to further establish causality between PCB exposure and clinical effects in humans.
CRIS-Team Scopus Importer:2023-09-25
Keywords: HELPcB; Occupational exposure; Polychlorinated biphenyls